2015
DOI: 10.18632/oncotarget.5313
|View full text |Cite
|
Sign up to set email alerts
|

The herbal compound Songyou Yin (SYY) inhibits hepatocellular carcinoma growth and improves survival in models of chronic fibrosis via paracrine inhibition of activated hepatic stellate cells

Abstract: Chronic fibrosis is a major risk factor for the development of hepatocellular carcinoma (HCC). The pathological progression of hepatic fibrosis has been linked to cellular processes that promote tumor growth and metastasis. Several recent studies have highlighted the cross-talk between tumor cells and activated hepatic stellate cells (aHSCs) in HCC. The herbal compound Songyou Yin (SYY) is known to attenuate hepatoma cell invasion and metastasis via down-regulation of cytokine secretion by aHSCs. However the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…Chen [20,21] et al has shown that prostate cancer-derived CCN3 can induce M2 macrophage infiltration, relating to the construction of the prospective environment conducive to prostate cancer metastasis. Previously, we had reported that HSCs could interact with hepatoma cells via secretion of cytokines, which play a critical role in modulating the malignant phenotypic changes of HCC [22,23]. In the present study, we proved the infiltration of HSCs into the HCC milieu relating to CCN3 paracrine of HCC, and CCN3 could elevate the cytokines paracrined by HSCs relating to enhanced HCC malignancy, all of which indicate the important role of CCN3 in the crosstalk between HCC and HSCs.…”
Section: Discussionsupporting
confidence: 69%
“…Chen [20,21] et al has shown that prostate cancer-derived CCN3 can induce M2 macrophage infiltration, relating to the construction of the prospective environment conducive to prostate cancer metastasis. Previously, we had reported that HSCs could interact with hepatoma cells via secretion of cytokines, which play a critical role in modulating the malignant phenotypic changes of HCC [22,23]. In the present study, we proved the infiltration of HSCs into the HCC milieu relating to CCN3 paracrine of HCC, and CCN3 could elevate the cytokines paracrined by HSCs relating to enhanced HCC malignancy, all of which indicate the important role of CCN3 in the crosstalk between HCC and HSCs.…”
Section: Discussionsupporting
confidence: 69%
“…Hepatocellular carcinoma (HCC) is the most common type of primary liver cancer [ 1 , 2 ]. HCC ranks the fourth in the frequency of cancer in men [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chen [23, 24] et al has shown that prostate cancer-derived CCN3 can induce M2 macrophage infiltration, relating to the construction of the prospective environment conducive to prostate cancer metastasis. Previously, we had reported that HSCs could interact with hepatoma cells via secretion of cytokines, which play a critical role in modulating the malignant phenotypic changes of HCC [6, 25]. In the present study, we proved the infiltration of HSCs into the HCC milieu relating to CCN3 paracrine of HCC, and CCN3 could elevate the cytokines paracrined by HSCs relating to enhanced HCC malignancy, all of which indicate the important role of CCN3 in the crosstalk between HCC and HSCs.…”
Section: Discussionmentioning
confidence: 99%